A nickel-iron-manganese oxyhydroxide positive electrode precursor and its preparation method and application
Preparation of nickel-ferromanganese hydroxyoxide positive electrode precursor through co-precipitation method solves the problems of high cost of lithium batteries and insufficient research on the positive electrode materials of sodium batteries, improves the density and battery performance of nickel-ferromanganese hydroxyoxide, and achieves higher Yield and sodium ion intercalation efficiency.
Patent Information
- Application Number
- CN202310317362.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-03-23
AI Technical Summary
Due to the increasing cost of lithium batteries and the scarcity of lithium resources, there are few researches on the preparation process and precursors of existing sodium battery positive electrode materials, especially the application advantages of nickel ferromanganese hydroxyoxide as precursors have not been fully utilized.
The co-precipitation method is used to prepare the positive electrode precursor of nickel ferromanganese hydroxyoxide. By mixing the mixed solution and the base liquid under oxidation conditions for co-precipitation reaction, a nickel ferromanganese hydroxyoxide with a high proportion of metal ion mass is obtained. The nanosheet mosaic structure was obtained with a spherical morphology.
The true density and proportion of metal ions of nickel-ferromanganese hydroxyoxides have been improved, the yield of the precursor conversion to the positive electrode material has been improved, and the microscopic layered structure has been maintained, which has enhanced the embedded capacity of sodium ions and achieved better Battery performance.
Smart Images

Figure CN116332247B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of positive electrode precursors, and in particular relates to a nickel-iron-manganese hydroxide oxide positive electrode precursor and a preparation method and application thereof. Background Art
[0002] Currently, as lithium resources become scarce, the cost of lithium batteries continues to rise, limiting the development of lithium-ion batteries. Sodium batteries, a type of battery that charges and discharges by deintercalation of Na ions, have attracted much attention in recent years due to their low price, good theoretical capacity and other advantages. The core design of sodium-ion batteries is mainly the positive electrode material. Currently, there are many studies on high-gram capacity sodium-rich nickel-iron-manganese layered oxides with two-dimensional deintercalation, but there are fewer studies on their preparation processes or precursors. Among them, the sodium positive electrode material converted with nickel-iron-manganese hydroxide as a precursor has greater advantages than the traditional nickel-iron-manganese hydroxide as a precursor. Nickel-iron-manganese hydroxide has a higher mass ratio of metal ions than nickel-iron-manganese hydroxide, and obtaining a nickel-iron-manganese hydroxide with better performance has become a hot topic in this field. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a nickel-iron-manganese hydroxide oxide positive electrode precursor and a preparation method and application thereof. The nickel-iron-manganese hydroxide oxide provided by the present invention has good density performance.
[0004] The present invention provides a nickel-iron-manganese oxyhydroxide positive electrode precursor, wherein the crystallite size D of the (001) crystal plane of the nickel-iron-manganese oxyhydroxide positive electrode precursor is 001 It is 10~25nm.
[0005] Preferably, the chemical formula of the nickel-iron-manganese oxyhydroxide positive electrode precursor is:
[0006] Ni a Fe b Mn c OOH;
[0007] Among them, 0.15≤a≤0.35, 0.15≤b≤0.35, 0.25≤c≤0.66; a+b+c=1.
[0008] Preferably, the mass content of metal ions in the nickel-iron-manganese hydroxide oxide positive electrode precursor is 50% to 70%.
[0009] Preferably, the nickel-iron-manganese hydroxide oxide positive electrode precursor is a spherical morphology inlaid with nanosheets; the average thickness of the nanosheets is 100 to 350 nm.
[0010] Preferably, the tap density of the nickel-iron-manganese hydroxide positive electrode precursor is 0.75 to 1.2 g / cm3 The bulk density of the nickel-iron-manganese hydroxide positive electrode precursor is 0.4 to 0.7 g / cm 3 .
[0011] The present invention provides a method for preparing a nickel-iron-manganese oxyhydroxide positive electrode precursor, comprising:
[0012] The mixed solution and the base solution are mixed to obtain a suspension;
[0013] Under oxidizing conditions, the suspension is subjected to a coprecipitation reaction to obtain a nickel-iron-manganese hydroxide oxide positive electrode precursor;
[0014] The mixed solution comprises: a metal source and a solvent;
[0015] The base liquid comprises: a complexing agent and a precipitating agent.
[0016] Preferably, the oxidation conditions are selected from adding an oxidant and / or passing an oxygen-containing gas;
[0017] The oxidation conditions make the oxygen content in the supernatant of the suspension 5-20 mg / L.
[0018] Preferably, the coprecipitation reaction temperature is 40-70°C.
[0019] Preferably, after the coprecipitation reaction is completed, the method further comprises:
[0020] The obtained reaction product is dried to obtain a nickel-iron-manganese hydroxide oxide positive electrode precursor;
[0021] The drying temperature is 100-200°C.
[0022] The present invention provides a positive electrode material, which is prepared from a material including the nickel-iron-manganese hydroxide oxide positive electrode precursor described in the above technical solution; or prepared from a material including the nickel-iron-manganese hydroxide oxide positive electrode precursor prepared by the method described in the above technical solution.
[0023] The present invention provides a sodium battery, comprising: the positive electrode material described in the above technical solution.
[0024] In the present invention, it is considered that the nickel-iron-manganese oxyhydroxide is a secondary ball inlaid with primary nanosheets, and under the condition of the same volume of the secondary ball, the thicker the primary nanosheet, the greater the true density of the secondary ball, which will directly affect the tap density of the material, thereby affecting the subsequent yield of the material. The thickness of the primary nanosheet depends on the crystallite scale in the c-axis direction, and the (001) crystal plane of the nickel-iron-manganese oxyhydroxide is the crystal plane of the transition metal layer on its c-axis. Therefore, without testing the tap density, bulk density or SEM, it is only necessary to measure the crystallite size D of the (001) crystal plane in the XRD of the nickel-iron-manganese oxyhydroxide.001 That is, the thickness of the primary nanosheet can be benchmarked, so as to know the true density trend of the overall secondary spherical particles and judge the quality of the material. The nickel-iron-manganese hydroxide oxide provided by the present invention has better performance.
[0025] The nickel iron manganese hydroxide (Ni a Fe b Mn c OOH) ternary sodium precursor, compared with the traditional nickel iron manganese hydroxide (Ni a Fe b Mn c (OH)3), has a higher mass ratio of metal ions, reaching 50-70%. Under the same mass, the yield of the precursor to the positive electrode conversion process is increased to 5-15%. At the same time, the retained OH - The microscopic layered structure can be maintained so that the interplanar spacing of the (001) crystal plane is maintained at It helps in the subsequent co-firing process with the sodium source and the embedding of sodium ions, thereby obtaining better performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of the product prepared in Example 1 of the present invention;
[0027] Figure 2 This is a SEM image of the product prepared in Example 1 of the present invention;
[0028] Figure 3 This is the XRD pattern of the product prepared in Example 1 of the present invention;
[0029] Figure 4 This is a SEM image of the product prepared in Comparative Example 1 of the present invention;
[0030] Figure 5 This is a SEM image of the product prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The present invention provides a nickel-iron-manganese oxyhydroxide positive electrode precursor, wherein the crystallite size D of the (001) crystal plane of the nickel-iron-manganese oxyhydroxide positive electrode precursor is 001 It is 10~25nm.
[0033] In the present invention, the crystallite size D of the (001) crystal plane is001 It refers to the size of the continuous lattice fringes of the crystal particles along the (001) direction of the crystal plane, which can be obtained by XRD (X-ray diffraction) detection.
[0034] In the present invention, the D 001 is 10 to 25 nm, preferably 15 to 20 nm. 001 Preferably ≥10nm, more preferably D 001 ≥13nm.
[0035] In the present invention, the chemical formula of the nickel-iron-manganese oxyhydroxide positive electrode precursor is preferably:
[0036] Ni a Fe b Mn c OOH;
[0037] Among them, 0.15≤a≤0.35, 0.15≤b≤0.35, 0.25≤c≤0.66; a+b+c=1.
[0038] In the present invention, a, b and c refer to molar ratios.
[0039] In the present invention, a is preferably 0.2 to 0.3, more preferably 0.25; b is preferably 0.2 to 0.3, more preferably 0.25; c is preferably 0.3 to 0.6, more preferably 0.4 to 0.5.
[0040] In the present invention, the mass content of metal ions in the nickel-iron-manganese oxyhydroxide positive electrode precursor is preferably 50-70%, more preferably 55-65%, and most preferably 60%.
[0041] In the present invention, the nickel iron manganese hydroxide positive electrode precursor is preferably a spherical morphology inlaid with nanosheets; the average thickness of the nanosheets is preferably 250 to 350 nm, more preferably 280 to 320 nm, and most preferably 300 nm; the cross-section of the spherical morphology is preferably a porous structure, and the porous structure is preferably a uniform porous structure.
[0042] In the present invention, the tap density of the nickel-iron-manganese oxyhydroxide positive electrode precursor is preferably 0.75 to 1.2 g / cm 3 , more preferably 0.8 to 1.1 g / cm 3 , and most preferably 0.9 to 1 g / cm 3 .
[0043] In the present invention, the bulk density of the nickel-iron-manganese oxyhydroxide positive electrode precursor is preferably 0.4 to 0.7 g / cm 3 , more preferably 0.5 to 0.6 g / cm3 .
[0044] The present invention provides a method for preparing a nickel-iron-manganese oxyhydroxide positive electrode precursor, comprising:
[0045] The nickel-iron-manganese hydroxide oxide positive electrode precursor was prepared by co-precipitation method.
[0046] In the present invention, the coprecipitation method preferably comprises:
[0047] The mixed solution and the base solution are mixed to obtain a suspension;
[0048] Under oxidizing conditions, the suspension is subjected to a coprecipitation reaction to obtain a nickel-iron-manganese hydroxide oxide positive electrode precursor.
[0049] In the present invention, the mixed solution comprises a metal source and a solvent; the metal source is selected from a nickel source, an iron source and a manganese source; the nickel source is preferably selected from one or more of nickel nitrate, nickel chloride, nickel acetate and nickel sulfate; the iron source is preferably selected from one or more of ferric nitrate, ferric chloride, ferric acetate and ferric sulfate; the manganese source is preferably selected from one or more of manganese nitrate, manganese chloride, manganese acetate and manganese sulfate.
[0050] In the present invention, the molar ratio of the nickel source, the iron source and the manganese source can be prepared according to the molar ratio of nickel, iron and manganese in the pre-obtained nickel-iron-manganese hydroxide oxide positive electrode precursor.
[0051] In the present invention, the solvent is preferably selected from water and / or ethanol.
[0052] In the present invention, the concentrations of the nickel source, the iron source and the manganese source in the mixed solution are independently preferably 0.2 to 1 mol / L, more preferably 0.4 to 0.8 mol / L, and most preferably 0.6 mol / L.
[0053] In the present invention, the base liquid includes a complexing agent and a precipitant; the complexing agent is preferably selected from one or more of ammonia water, sodium citrate solution, tetrasodium ethylenediaminetetraacetate solution, and disodium ethylenediaminetetraacetate solution; the mass concentration of the ammonia water is preferably 1-10%, more preferably 2-8%, more preferably 3-6%, and most preferably 4-5%; the mass concentration of the sodium citrate solution (the solvent is water) is preferably 8-42%, more preferably 10-40%, more preferably 20-30%, and most preferably 25%; the mass concentration of the disodium ethylenediaminetetraacetate solution (the solvent is water) is preferably 1-12%, more preferably 2-10%, more preferably 3-8%, more preferably 4-6%, and most preferably 5%; the mass concentration of the tetrasodium ethylenediaminetetraacetate solution (the solvent is water) is preferably 2-35%, more preferably 5-30%, more preferably 10-25%, and most preferably 15-20%.
[0054] In the present invention, the precipitant is preferably selected from one or more of an alkaline solution (the solvent is water) and water; the alkaline solution is preferably selected from a sodium hydroxide solution and / or a potassium hydroxide solution; the mass concentration of the alkaline solution is preferably 15-45%, more preferably 20-40%, more preferably 25-35%, and most preferably 30%.
[0055] In the present invention, the mass ratio of the complexing agent to the precipitating agent is preferably (1-5):(5-1), more preferably (2-4):(4-2), and most preferably 3:3.
[0056] In the present invention, the mass ratio of the mixed solution to the base solution is preferably (1-5):(5-1), more preferably (2-4):(4-2), and most preferably 3:3.
[0057] In the present invention, the coprecipitation reaction is preferably carried out under a protective atmosphere.
[0058] In the present invention, the oxidation conditions are preferably selected from adding an oxidant and / or passing an oxygen-containing gas; the oxidant is preferably selected from one or more of hydrogen peroxide, sodium persulfate, sodium peroxide and ozone; the oxygen-containing gas is preferably oxygen; the oxidation conditions are preferably such that the amount of dissolved oxygen in the supernatant of the suspension is 5 to 20 mg / L, more preferably 10 to 15 mg / L.
[0059] In the present invention, the pH value of the coprecipitation reaction is preferably 9-13, more preferably 10-12, and most preferably 11; the temperature of the coprecipitation reaction is preferably 40-70°C, more preferably 50-60°C, and most preferably 55°C; the coprecipitation reaction is preferably carried out under stirring; the stirring speed is preferably 600-1100r / min, more preferably 700-1000r / min, and most preferably 800-900r / min; the coprecipitation reaction time is preferably 50-300h, more preferably 100-200h, and most preferably 150h.
[0060] In the present invention, after the coprecipitation reaction is completed, it is preferred that the following steps are further included:
[0061] The obtained reaction product is washed, filtered and dried to obtain a nickel-iron-manganese hydroxide oxide positive electrode precursor.
[0062] In the present invention, the drying is preferably carried out in air; the drying temperature is preferably 100-200°C, more preferably 120-180°C, most preferably 140-160°C; the drying time is preferably 4-16h, more preferably 8-16h, more preferably 10-14h, most preferably 12h.
[0063] In the present invention, by appropriately adding an oxidant / oxygen, increasing the coprecipitation temperature and the drying temperature, the mass proportion of metal ions in the nickel-iron-manganese hydroxide oxide can be increased, thereby increasing the yield of the precursor converted into the positive electrode material.
[0064] The present invention provides a positive electrode material, which is prepared from a material including the nickel-iron-manganese hydroxide oxide positive electrode precursor described in the above technical solution; or prepared from a material including the nickel-iron-manganese hydroxide oxide positive electrode precursor prepared by the method described in the above technical solution.
[0065] In the present invention, the positive electrode material is preferably a sodium-rich layered oxide, and the preparation method of the positive electrode material preferably includes:
[0066] The nickel-iron-manganese hydroxide oxide positive electrode precursor and sodium carbonate are mixed and then sintered.
[0067] In the present invention, the ratio of the molar number of sodium element in the sodium carbonate to the total molar number of metal elements in the nickel iron manganese hydroxide positive electrode precursor is preferably (0.67-1.25):1, more preferably (0.8-1.1):1, and most preferably 1:1.
[0068] In the present invention, the sintering temperature is preferably 800-1000°C, more preferably 800-900°C, and most preferably 850°C; the sintering time is preferably 10-15h, more preferably 11-14h, and most preferably 12h; the heating rate during the sintering process is preferably 1-5°C / min, more preferably 2-4°C / min, and most preferably 2°C / min.
[0069] The present invention provides a sodium battery, comprising: the positive electrode material described in the above technical solution.
[0070] The present invention has no particular limitation on the preparation method of the sodium battery, and those skilled in the art can select a suitable method to prepare the desired sodium battery according to actual needs.
[0071] In the present invention, the crystallite size D of the (001) crystal plane in the XRD of nickel-iron-manganese hydroxide oxide is measured. 001 , it is possible to benchmark the thickness of the primary nanosheets, thereby knowing the true density trend of the overall secondary spherical particles. By changing the reaction conditions to design nickel-iron-manganese hydroxide oxides with large (001) crystal plane sizes, the true density, tap density or loose density can be increased, thereby increasing the yield of precursor conversion to positive electrode materials.
[0072] The nickel iron manganese hydroxide (Ni a Fe b Mn c OOH) ternary sodium precursor, compared with the traditional nickel iron manganese hydroxide (Nia Fe b Mn c (OH)3), has a higher mass ratio of metal ions, reaching 50-70%. Under the same mass, the yield of the precursor to the positive electrode conversion process is increased to 5-15%. At the same time, the retained OH - The microscopic layered structure can be maintained so that the interplanar spacing of the (001) crystal plane is maintained at It helps in the subsequent co-firing process with the sodium source and the embedding of sodium ions, thereby achieving better performance.
[0073] The present invention can obtain the crystallite size of the (001) crystal plane by refining the XRD spectrum of the nickel-iron-manganese hydroxide oxide. In the unit cell structure, the (001) crystal plane refers to the plane of the transition metal layer along the c-axis. Therefore, the continuity of the (001) crystal plane determines the thickness of the primary nanosheet. Under the condition of the same secondary sphere volume, the thicker the primary nanosheet, the smaller the gap left in the secondary sphere, the higher the corresponding true density, the higher the filling amount under the same volume, and the higher the yield. The present invention only needs to measure the D 001 By comparing the size of the materials, it is possible to compare the density trends of the materials without testing the density, thus saving the corresponding testing costs.
[0074] Example 1
[0075] Ni was prepared by co-precipitation method 0.33 Fe 0.33 Mn 0.33 OOH:
[0076] Nickel sulfate, iron sulfate and manganese sulfate were added to distilled water at a molar ratio of 1:1:1 to prepare a mixed solution A, wherein the solubility of nickel sulfate, iron sulfate and manganese sulfate in the mixed solution A was 0.5 mol / L respectively, and a sodium citrate solution with a mass solubility of 20% and a sodium hydroxide solution with a mass solubility of 25% were prepared at a mass ratio of 1:1 to prepare a base solution B; the mixed solution A and the solution B were mixed in a reactor at a mass ratio of 1:1 to obtain a suspension solution C, and oxygen was introduced into the suspension C to maintain the dissolved oxygen of the supernatant at 8.67 mg / L, and a coprecipitation reaction was carried out for 100 hours under the conditions of pH 12.5, temperature 60°C and stirring speed 800 r / min, followed by washing and drying at 180°C in air for 8 hours to obtain Ni 0.33 Fe 0.33 Mn 0.33 OOH.
[0077] The Ni prepared in Example 1 0.33 Fe 0.33 Mn 0.33 OOH was tested by scanning electron microscope, and the test results were as follows Figure 1 and Figure 2 , it can be seen that the primary nanosheets of the material are in the form of sheets with a thickness of 100 to 350 nm, and the secondary spheres are in the form of regular spheres, which are inlaid with the primary nanosheets.
[0078] The Ni prepared in Example 1 0.33 Fe 0.33 Mn 0.33 OOH was subjected to X-ray diffraction, and the test results were as follows Figure 3 As shown, it can be seen that Ni 0.33 Fe 0.33 Mn 0.33 The crystal structure of OOH is the same as that of FeOOH, and the FeOOH standard card is used for comparison.
[0079] The Ni prepared in Example 1 0.33 Fe 0.33 Mn 0.33 D of OOH 001 , tap density and bulk density were tested by Rietveld method refinement of XRD spectrum, Dandong Better Tester (GB / T5162-2006, test conditions: 50g sample transferred to 100mL measuring cylinder, 200 times per minute, tapped 3000 times, and then density calculated) and Scott instrument test (GB / T1479.2, density calculated by pouring 25ml volume sample through a funnel); the test results are shown in Table 1.
[0080] Example 2
[0081] Ni was prepared by co-precipitation method 0.22 Fe 0.34 Mn 0.44 OOH:
[0082] Nickel sulfate, iron sulfate and manganese sulfate were added to distilled water in a molar ratio of 1:1.54:2 to prepare a mixed solution A, wherein the solubilities of nickel sulfate, iron sulfate and manganese sulfate in the mixed solution A were 0.33 mol / L, 0.52 mol / L and 0.67 mol / L, respectively; a sodium citrate solution with a mass solubility of 20% and a sodium hydroxide solution with a mass solubility of 25% were prepared in a mass ratio of 1:1 to prepare a base solution B; the mixed solution A and the base solution B were mixed in a reactor in a mass ratio of 1:1 to obtain a suspension solution C, and oxygen was introduced into the suspension C to maintain the dissolved oxygen of the supernatant at 8.66 mg / L, and a coprecipitation reaction was carried out for 100 hours at a pH of 12.5, a temperature of 60°C and a stirring speed of 800 r / min, followed by washing and drying in air at 180°C for 8 hours to obtain Ni 0.22 Fe 0.34 Mn 0.44 OOH.
[0083] Example 2 Ni prepared 0.22 Fe 0.34 Mn 0.44 D of OOH 001 , tap density and bulk density are shown in Table 1.
[0084] Example 3
[0085] Ni was prepared by co-precipitation method 0.33 Fe 0.33 Mn 0.33 OOH:
[0086] Nickel sulfate, iron sulfate and manganese sulfate were added to distilled water at a molar ratio of 1:1:1 to prepare mixed solution A, in which the solubility of nickel sulfate, iron sulfate and manganese sulfate in mixed solution A was 0.5 mol / L respectively, and sodium citrate solution with a mass solubility of 20% and sodium hydroxide solution with a mass solubility of 25% were prepared at a mass ratio of 1:1 to prepare base solution B. Mixed solution A and base solution B were mixed in a reactor at a mass ratio of 1:1 to obtain suspension solution C, and oxygen was introduced into the suspension C to maintain the dissolved oxygen of the supernatant at 12.2 mg / L, and a coprecipitation reaction was carried out for 95 hours at a pH of 12.5, a temperature of 60°C and a stirring speed of 800 r / min, followed by washing and drying at 180°C in air for 8 hours to obtain Ni 0.33 Fe 0.33 Mn 0.33 OOH.
[0087] Example 3 Ni prepared 0.33 Fe 0.33 Mn 0.33 D of OOH 001 , tap density and bulk density are shown in Table 1.
[0088] Example 4
[0089] Ni was prepared by co-precipitation method 0.33 Fe 0.33 Mn 0.33 OOH:
[0090] Nickel sulfate, iron sulfate and manganese sulfate were added to distilled water at a molar ratio of 1:1:1 to prepare mixed solution A, in which the solubility of nickel sulfate, iron sulfate and manganese sulfate in mixed solution A was 0.5 mol / L respectively, and sodium citrate solution with a mass solubility of 20% and sodium hydroxide solution with a mass solubility of 25% were prepared at a mass ratio of 1:1 to prepare base solution B. Mixed solution A and base solution B were mixed in a reactor at a mass ratio of 1:1 to obtain suspension solution C, and oxygen was introduced into the suspension C to maintain the dissolved oxygen of the supernatant at 6 mg / L, and a coprecipitation reaction was carried out for 100 hours at a pH of 12.5, a temperature of 70°C and a stirring speed of 800 r / min, followed by washing and drying at 140°C in air for 8 hours to obtain Ni 0.33 Fe 0.33 Mn 0.33 OOH.
[0091] Example 4 Ni prepared 0.22 Fe 0.34 Mn 0.44 D of OOH 001 , tap density and bulk density are shown in Table 1.
[0092] Example 5
[0093] Ni was prepared by co-precipitation method 0.22 Fe 0.34 Mn 0.44 OOH:
[0094] Nickel sulfate, iron sulfate and manganese sulfate were added to distilled water at a molar ratio of 1:1.54:2 to prepare mixed solution A, in which the solubility of nickel sulfate, iron sulfate and manganese sulfate in mixed solution A were 0.33 mol / L, 0.52 mol / L and 0.67 mol / L respectively, and a sodium citrate solution with a mass solubility of 20% and a sodium hydroxide solution with a mass solubility of 25% were prepared at a mass ratio of 1:1 to prepare base solution B. Mixed solution A and base solution B were mixed in a reactor at a mass ratio of 1:1 to obtain suspension solution C, and oxygen was introduced into the suspension C to maintain the dissolved oxygen of the supernatant at 8.65 mg / L, and a coprecipitation reaction was carried out for 110 hours at a pH of 12.5, a temperature of 60°C and a stirring speed of 800 r / min, followed by washing and drying at 180°C in air for 8 hours to obtain Ni 0.22 Fe 0.34 Mn 0.44 OOH.
[0095] Example 5: Ni prepared 0.22 Fe 0.34 Mn 0.44 D of OOH 001 , tap density and bulk density are shown in Table 1.
[0096] Comparative Example 1
[0097] Ni was prepared by co-precipitation method 0.33 Fe 0.33 Mn 0.33 (OH)3:
[0098] Nickel sulfate, iron sulfate and manganese sulfate were added to distilled water at a molar ratio of 1:1:1 to prepare mixed solution A, in which the solubility of nickel sulfate, iron sulfate and manganese sulfate in mixed solution A was 0.5 mol / L respectively, and sodium citrate solution with a mass solubility of 20% and sodium hydroxide solution with a mass solubility of 25% were prepared at a mass ratio of 1:1 to prepare base solution B. Mixed solution A and base solution B were mixed in a reactor at a mass ratio of 1:1 to obtain suspension solution C, and a coprecipitation reaction was carried out for 70 hours at a pH value of 9, a temperature of 40°C and a stirring speed of 400 r / min, followed by washing and drying at 180°C in air for 8 hours to obtain Ni 0.33 Fe 0.33 Mn 0.33 (OH)3.
[0099] Ni prepared in Comparative Example 1 0.33 Fe 0.33 Mn 0.33 The scanning electron microscope image of (OH)3 is as follows Figure 4 and 5 As shown, it can be seen that the volume of the secondary sphere is not much different from that in Example 1, but the thickness of the primary nanosheet is relatively thin.
[0100] Ni prepared in Comparative Example 1 0.33 Fe 0.33 Mn 0.33 (OH)3D 001 , tap density and bulk density are shown in Table 1.
[0101] Table 1 D of products prepared in Examples and Comparative Examples 001 , tap density and bulk density test results
[0102] <![CDATA[D 001 (nm)]]> <![CDATA[Tap density (g / cm 3 )]]> <![CDATA[Bulk density (g / cm 3 )]]> Example 1 17.795 1.1 0.62 Example 2 13.511 0.9 0.5 Example 3 13.985 1 0.53 Example 4 15.774 1.05 0.6 Example 5 14.121 0.98 0.54 Comparative Example 1 11.514 0.65 0.38
[0103] The nickel iron manganese hydroxide (Ni a Fe b Mn c OOH) ternary sodium precursor, compared with the traditional nickel iron manganese hydroxide (Ni a Fe b Mn c (OH)3), has a higher mass ratio of metal ions, reaching 50-70%. Under the same mass, the yield of the precursor to the positive electrode conversion process is increased to 5-15%. At the same time, the retained OH- The microscopic layered structure can be maintained so that the interplanar spacing of the (001) crystal plane is maintained at It helps in the subsequent co-firing process with the sodium source and the embedding of sodium ions, thereby achieving better performance.
[0104] Although the present invention has been described and illustrated with reference to specific embodiments of the present invention, these descriptions and illustrations do not limit the present invention. It will be clearly understood by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention as defined by the appended claims, so that specific circumstances, materials, material compositions, materials, methods or processes are suitable for the goals, spirit and scope of the present application. All such modifications are intended to be within the scope of the appended claims. Although the methods disclosed herein have been described with reference to specific operations performed in a specific order, it should be understood that these operations may be combined, subdivided or reordered to form equivalent methods without departing from the teachings of the present invention. Therefore, unless specifically indicated herein, the order and grouping of operations are not limitations of the present application.
Claims
1. A nickel-iron-manganese oxyhydroxide positive electrode precursor, characterized in that: The crystallite size D of the (001) crystal plane of the nickel-iron-manganese oxyhydroxide positive electrode precursor is 001 10~25nm; The chemical formula of the nickel-iron-manganese oxyhydroxide positive electrode precursor is: In a Want b Mn c OOH; Among them, 0.15≤a≤0.35, 0.15≤b≤0.35, 0.25≤c≤0.66; a+b+c =1; The mass content of metal ions in the nickel-iron-manganese hydroxide oxide positive electrode precursor is 50% to 70%.
2. The nickel-iron-manganese oxyhydroxide positive electrode precursor according to claim 1, characterized in that: The nickel-iron-manganese hydroxide oxide positive electrode precursor is a spherical morphology inlaid with nanosheets; the average thickness of the nanosheets is 100-350nm.
3. The nickel-iron-manganese oxyhydroxide positive electrode precursor according to claim 1, characterized in that: The tap density of the nickel-iron-manganese hydroxide positive electrode precursor is 0.75-1.2 g / cm 3 The bulk density of the nickel-iron-manganese hydroxide positive electrode precursor is 0.4-0.7 g / cm 3 .
4. A method for preparing the nickel-iron-manganese oxyhydroxide positive electrode precursor according to any one of claims 1 to 3, comprising: The mixed solution and the base solution are mixed to obtain a suspension; Under oxidizing conditions, the suspension is subjected to a coprecipitation reaction to obtain a nickel-iron-manganese hydroxide oxide positive electrode precursor; The mixed solution comprises: a metal source and a solvent; The base liquid comprises: a complexing agent and a precipitating agent.
5. The preparation method according to claim 4, characterized in that: The oxidation conditions are selected from adding an oxidant and / or passing an oxygen-containing gas; The oxidation conditions make the oxygen content in the supernatant of the suspension 5-20 mg / L.
6. The preparation method according to claim 4, characterized in that: The temperature of the coprecipitation reaction is 40-70°C.
7. The preparation method according to claim 4, characterized in that: After the coprecipitation reaction is completed, the following steps are further included: The obtained reaction product is dried to obtain a nickel-iron-manganese hydroxide oxide positive electrode precursor; The drying temperature is 100-200°C.
8. A positive electrode material, prepared from a material comprising the nickel-iron-manganese hydroxide oxide positive electrode precursor according to any one of claims 1 to 3; or prepared from a material comprising the nickel-iron-manganese hydroxide oxide positive electrode precursor prepared by the preparation method according to any one of claims 4 to 7.
9. A sodium battery comprising: The positive electrode material according to claim 8.
Citation Information
Patent Citations
Composite oxyhydroxide of nickel-manganese and production method thereof, and use thereof
JP2016020283A